Anatomical distal biceps tendon reconstruction with a semitendinosus autograft - Siva Srivastava Garika; Asjad Mahmood; Ravi Mittal; Vijay Kumar Digge (Journal of Orthopaedic Reports)
Distal biceps tendon ruptures are relatively uncommon. In a chronic presentation, they are challenging to treat due to tendon retraction, fibrosis and adhesions. Reconstruction using autografts is the preferred method of management in these cases. Although many methods of reconstruction have been described in the literature, reconstructing in an anatomical way would yield better outcomes.We describe a case of a chronic retracted distal biceps tendon rupture reconstructed by a semitendinosus autograft in an anatomic and cost-effective manner.